Interface Slip of the Steel Beam Strengthened with the CFRP Sheet under Temperature and Creep - Wenyu Hou; Yanfeng Li; Yongping Guan (Advances in Materials Science and Engineering)
This paper studied the interface slip between the CFRP sheet and the steel beam under the action of temperature and creep. The formulas of the interface slip were established by using the elastic method and energy variational method, respectively, and the accuracy of the formulas was verified by finite element analysis Abaqus. The results showed that when the creep was not taken into account, the interface slip was the maximum at the end of the beam and the minimum at the middle of the span. When the temperature increased to 5°C, the slip increased about 0.005 mm. And when the thickness of the CFRP sheet increased to 0.05 mm, the slip increased about 0.003 mm. When the creep was taken into account, the interface slip increased with the increase of load and decreased with the increase of stiffness. When the stiffness reached about 10 ka, the variation of the stiffness on the slip was basically unchanged.